Paraneoplastic pemphigus involved oral mucosa only: a case report and literature review - Xixi Yu; Mei Yang; Caixia Wang; Wanchun Wang; Tingting Zhu; Yang Liu (Frontiers in Medicine)
Paraneoplastic pemphigus (PNP) is a rare and potentially fatal autoimmune disease that primarily affects the mucocutaneous tissues. Here we present the clinical features of a patient with the lichenoid variant of PNP involving the oral mucosa only. The patient exhibited clinical manifestations resembling both lichen planus and pemphigus, yet these lesions remained unresponsive to corticosteroid therapy. A chest computed tomography (CT) scan revealed Castleman disease. Following surgical removal of the tumor, the patient’s oral mucosa healed completely, with no recurrence observed in a 4-year follow-up period. These findings emphasize the importance of considering PNP as a potential diagnosis in patients with refractory oral erosions displaying lichen planus-like and pemphigus-like features, particularly when unresponsive to corticosteroid therapy. A thoracic-abdominal-pelvic CT scan is recommended to facilitate accurate diagnosis and appropriate treatment.